Organizational based self-esteem: A systematic literature review (Asian Journal of Economics and Business Management, 2023)
In the era of Society 5.0, businesses confront numerous opportunities and dangers. Despite the company's efforts to remain competitive in its industry, it faces numerous internal threats. Therefore, employees as valuable assets in the operation of the business require special treatment. Companies must prioritize employee welfare by assuring employees' psychological health. Organization-based self-esteem may be said to have been developed by employees who are invested in the organization, eligible for advancement, and have faith that their requirements will be met there. They are more likely to take pride in their work if they value themselves and their contributions to the company.  This study uses a Systematic Literature Review scheme aimed at reviewing research previously related to Organizational Based Self Esteem within the scope of Human Resource Management. There are 120 pieces of research literature found and then filtered using the PRISMA method. Using the PICO method in collecting data using 2 sources, namely Science Direct and Emerald Insight. The results of filtering and data inclusion obtained 30 journals as material for the final review. Through this study, it was concluded that companies that have adopted self-esteem-based organizations (OBSE) realize that employees tend to feel more valued, supported, and motivated. Thus, having better performance, higher productivity, and greater job satisfaction.